Criminal Liability in Transferring Fiduciary Security Objects With out the Consent of the Fiduciary - Median Dwi Raharjo (Faculty of Law, Universitas Lampung, 2020)
The concept of criminal offense related to the transfer of fiduciary objects by fiduciary givers without the approval of the fiduciary as stipulated in Article 36 of the Fiduciary Law is a dualistic matter, because the attachment between fiduciary givers and fiduciary recipients is based on civil law relations contained in the fiduciary agreement but on the other hand it is formulated as a criminal act. The problem in this study is how is the criminal responsibility of the fiduciary who diverts the object of fiduciary collateral without the consent of the fiduciary recipient? and what is the basis for the Judge's consideration in imposing a judgment on the fiduciary who diverts the object of fiduciary guarantee without the consent of the fiduciary recipient? This study uses a normative-empirical legal research approach. The data used are primary and secondary data. Data analysis is done using qualitative analysis. The results of this study. Fiduciary criminal liability that transfers the object of fiduciary collateral without written approval from the fiduciary recipient as referred to in the Number case decision. 43/Pid.B/2018/PN.Kbu is based on the mistake of the Defendant as the fiduciary giver which includes intentions or negligence, while the acts committed are prohibited and threatened with criminal acts. Furthermore, the mistakes made can be proven that the Defendant has the ability to account for his actions and there is no forgiving reason.